An AIREless Breath: Pneumonitis Caused by Impaired Central Immune Tolerance - Ferré, Elise M. N.; Lionakis, Michail S. (Frontiers in Immunology, 2021)
Autoimmune-polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), a monogenic disorder caused by biallelic mutations in the AIRE gene, has historically been defined by the development of chronic mucocutaneous candidiasis together with autoimmune endocrinopathies, primarily hypoparathyroidism and adrenal insufficiency. Recent work has drawn attention to the development of life-threatening non-endocrine manifestations such as autoimmune pneumonitis, which has previously been poorly recognized and under-reported. In this review, we present the clinical, radiographic, autoantibody, and pulmonary function abnormalities associated with APECED pneumonitis, we highlight the cellular and molecular basis of the autoimmune attack in the AIRE-deficient lung, and we provide a diagnostic and a therapeutic roadmap for patients with APECED pneumonitis. Beyond APECED, we discuss the relevance and potential broader applicability of these findings to other interstitial lung diseases seen in secondary AIRE deficiency states such as thymoma and RAG deficiency or in common polygenic autoimmune disorders such as idiopathic Sjögren’s syndrome.